Better Students Ask More Questions.
In factorizing the expression a^4+a^2*b^2+b^4, we find that A. (a^2–b^2) is a...
1 Answer | add yours
`x = a^2`
`y = b^2`
So we can rewrite the expression as;
`f(x) = x^2+xy+y^2`
`f(x) = x^2+2xy-xy+y^2`
`f(x) = (x^2+2xy+y^2)-xy`
We know that `x^2+2xy+y^2 = (x+y)^2`
`f(x) = (x+y)^2-xy`
Substituting original values of x and y yields;
`(x+y)^2-xy = (a^2+b^2)^2-a^2b^2`
So the correct answer is D)
Posted by jeew-m on September 2, 2013 at 3:40 AM (Answer #1)
Join to answer this question
Join a community of thousands of dedicated teachers and students.